2020
DOI: 10.1159/000511908
|View full text |Cite
|
Sign up to set email alerts
|

The Elevation in Preoperative Procalcitonin Is Associated with a Poor Prognosis for Patients Undergoing Resection for Colorectal Cancer

Abstract: <b><i>Background:</i></b> Procalcitonin (PCT) is a well-known marker for bacterial infection; however, the clinical significance of PCT in the long-term prognosis after colorectal cancer (CRC) surgery remains unclear. <b><i>Methods:</i></b> This is a retrospective review of 277 patients that underwent CRC surgery to investigate the relationship between preoperative PCT, clinicopathological condition, cancer-specific overall survival (OS), and relapse-free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In a prospective population-based study that enrolled 3322 patients [32], the baseline PCT was found to be significantly associated with all-cause mortality and cancer-related mortality in men after a median follow-up time of 16.2 years. In a retrospective study of 277 colorectal cancer patients who received surgery, the pre-operative PCT concentration was identified as a significant predictor for cancer-specific survival in stages I to III of the disease [15]. In another retrospective study consisting of 95 metastatic NSCLC patients who received immune-check point inhibitors, a baseline PCT concentration of > 0.1 mg/L was confirmed to result in significantly worse outcomes in terms of OS [33].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a prospective population-based study that enrolled 3322 patients [32], the baseline PCT was found to be significantly associated with all-cause mortality and cancer-related mortality in men after a median follow-up time of 16.2 years. In a retrospective study of 277 colorectal cancer patients who received surgery, the pre-operative PCT concentration was identified as a significant predictor for cancer-specific survival in stages I to III of the disease [15]. In another retrospective study consisting of 95 metastatic NSCLC patients who received immune-check point inhibitors, a baseline PCT concentration of > 0.1 mg/L was confirmed to result in significantly worse outcomes in terms of OS [33].…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, many studies have highlighted the predictive role of PCT on the prognosis of several cancers, such as medullary thyroid cancer, NSCLC, colorectal cancer, neuroendocrine neoplasms, and so on [12][13][14][15]31]. In a prospective population-based study that enrolled 3322 patients [32], the baseline PCT was found to be significantly associated with all-cause mortality and cancer-related mortality in men after a median follow-up time of 16.2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, most previous studies have explored the prognostic value of CRP, PCT and IL-6 levels individually for CRC in the preoperative setting [ 4 , 5 ] and have yielded inconsistent results when considered together. For example, the study by Groblewska et al indicated that CRP was the only independent risk factor for survival when compared to IL-6 [ 6 ]; in contrast, the study by Lee et al suggested that IL-6 but not CRP, was an independent risk factor for disease-free survival (DFS) in stage III patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%